The Dynamics of AI Technology Utilization in Arabic Language Skills Learning in the Merdeka Curriculum - Rifqi Aulia Rahman; Nukman, Nukman; Ahmad Fadhel Syakir Hidayat; Amrulloh Khoirul Ma'arif; Zulfi Irkhamni (PT. Berkah Smart Academica, 2025)
The utilization of Artificial Intelligence (AI) in Arabic language learning is crucial in the Society 5.0 era, where technology significantly enhances educational quality. Arabic language learning faces challenges, particularly in grammatical aspects, translation, and speaking and writing skills, which require a more adaptive and practical approach. This study examines AI's application in Arabic language learning within the Merdeka Curriculum, focusing on technologies such as Artificial Intelligence Markup Language (AIML), E-Muhadathah, GAFE, Powtoon, and Alexa. A qualitative library research approach is employed, with data analyzed descriptively through relevant themes. The findings indicate that AI can optimize Arabic language teaching by reducing human error, speeding up the evaluation process, and supporting the development of students' Arabic language skills. However, challenges related to costs, machine creativity limitations, and adequate infrastructure must be addressed. In conclusion, AI offers a potential solution to enhance Arabic language learning. However, the success of learning still depends on the active involvement of both students and teachers in the process.